2018
DOI: 10.1038/s41598-018-30527-1
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in Drosophila melanogaster survival of Beauveria bassiana infection depends on core immune signaling

Abstract: In many animal species, females and males differ in physiology, lifespan, and immune function. The magnitude and direction of the sexual dimorphism in immune function varies greatly and the genetic and mechanistic bases for this dimorphism are often unknown. Here we show that Drosophila melanogaster females are more likely than males to die from infection with several strains of the fungal entomopathogen Beauveria bassiana. The sexual dimorphism is not exclusively due to barrier defenses and persists when flie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
38
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 56 publications
(60 reference statements)
10
38
2
Order By: Relevance
“…A better understanding of what leads to sexual dimorphism in immune defense may guide the use of B. bassiana in biological control efforts that may benefit from targeting female insects. Previous studies have suggested that D. melanogaster females are more susceptible to infection with B. bassiana infection compared to males (Taylor and Kimbrell 2007, Kubiak et al 2017, Shahrestani et al 2018. Using the same B. bassiana ARSEF 12460 pathogen, we previously found that female flies were more susceptible to infection than male flies in inbred fly lines (Shahrestani et al 2018), and this direction of sexual dimorphism was maintained whether the flies were sprayed or inoculated with the fungus, suggesting that grooming and barrier defenses are not fully responsible for sexual dimorphism in defense.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…A better understanding of what leads to sexual dimorphism in immune defense may guide the use of B. bassiana in biological control efforts that may benefit from targeting female insects. Previous studies have suggested that D. melanogaster females are more susceptible to infection with B. bassiana infection compared to males (Taylor and Kimbrell 2007, Kubiak et al 2017, Shahrestani et al 2018. Using the same B. bassiana ARSEF 12460 pathogen, we previously found that female flies were more susceptible to infection than male flies in inbred fly lines (Shahrestani et al 2018), and this direction of sexual dimorphism was maintained whether the flies were sprayed or inoculated with the fungus, suggesting that grooming and barrier defenses are not fully responsible for sexual dimorphism in defense.…”
Section: Discussionmentioning
confidence: 81%
“…Inoculation of flies with B. bassiana: Flies were inoculated with B. bassiana ARSEF 12460 Shahrestani & Vandenberg (Shahrestani et al 2018). Flies were briefly anesthetized with carbon dioxide (CO2) and measured in a microcentrifuge tube to 0.5 mL, which corresponds to approximately 50 flies/sex.…”
Section: Quantitative Trait Locus Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, systemic immune responses are mediated by peptidoglycan recognition and the activation of Imd in addition to the recognition of microbe-associated molecular patterns (MAMPs) through intra- and extracellular peptidoglycan recognition proteins (PGRPs). Previous studies have demonstrated distinct sexual dimorphisms between males and females in both the Imd and Toll-mediated systemic responses ( 42 44 ). In both cases, mated female flies are significantly more susceptible to bacterial pathogens during systemic infections by Gram-positive and Gram-negative bacteria in addition to fungal pathogens ( 42 , 43 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Protocols for the eradication of both are described in subsequent sections of this study. Drosophila exhibits marked sexual dimorphism in response to infection; female flies customarily have lower survival rates compared to males after infection (Duneau et al, ; Shahrestani et al, ). Additionally, mating status has a substantial impact on the outcome of infection, with mated females typically presenting with increased susceptibility and higher pathogen loads compared to virgin females (Schwenke & Lazzaro, ; Short & Lazzaro, ).…”
Section: Introductionmentioning
confidence: 99%